Effects of gamma radiation on the thermoanalytical, structural and pasting properties of black rice (Oryza sativa L.) flour - Ito, Vivian Cristina; Bet, Camila Delinski; Wojeicchowski, Jose Pedro; Demiate, Ivo Mottin; Fillet Spoto, Marta Helena; Schnitzler, Egon; Lacerda, Luiz Gustavo (Springer, 2018)
The effects of different doses of gamma radiation on the thermoanalytical, structural and pasting properties of black rice (Oryza sativa L.) flour were studied using thermogravimetry and derivative thermogravimetry (TG-DTG), differential scanning calorimetry, X-ray diffraction (XRD), field emission gun-scanning electron microscopy (FEG-SEM) and pasting properties (RVA) analysis. The thermogravimetric curves showed four mass losses. A small displacement was observed for the second loss, which occurred for the irradiated flours, compared to the control sample. The irradiated samples showed a slight decrease in the thermal parameters: initial temperature (T (o)), peak temperature (T (p)) and gelatinisation enthalpy (a-H-3). All the black rice flours exhibited A-type crystallinity pattern, and the gamma radiation did not change the XRD patterns or the degree of crystallinity. The micro-images obtained using FEG-SEM showed a composite of organic and heterogeneous material; after gamma radiation, some changes occurred, such as cracks, pores and smaller fragments. The pasting properties decreased significantly with irradiation. The decrease in setback and breakdown viscosity after irradiation suggested an indication that it may be possible to improve the quality of food based on black rice flours. Gamma radiation can be a useful tool to modify rice flours in order to suit various functionalities and to help meet the growing demands of the food industry.
Keywords: Black rice; Irradiation; Thermal analysis; Gelatinisation; Morphology; Crystallinity